Triple gauge boson production and dynamical symmetry breaking at the Next Linear Collider - Rosenfeld, Rogério [UNESP]; Zerwekh, Alfonso R. [UNESP] (Elsevier, 1998)
We study in a model independent way the role of a techniomega resonance in the process e+e-→ W+W-Z at the Next Linear Collider. © 1998 Elsevier Science B.V.